Test on Iron Recovery by Leaching and Magnetic Separation from a Laterite-type Gold Mine in Western Yunnan Province - Minghui GONG; Zuming NIE; Lei QI; Huixin DAI (Kuangchan zonghe liyong)
The present study focuses on the comprehensive utilization of resources, specifically examining a laterite oxidized gold deposit located in western Yunnan Province. In this gold ore, the Au grade is 1.72 g/t, accompanied by 17.50 g/t Ag and 28.19% TFe (with an mFe content of 11.52%), which belongs to a low-grade complex and refractory polymetallic gold ore. A technical route of "the whole mud cyanidation leaching of gold and silver in the sand separation system-low and high magnetic separation iron from leaching slags, and cyanidation leaching of gold and silver from the pre-selected coarse concentrate in the mud separation system" was proposed, for the coarse sand and pre-selected coarse concentrate produced by the process of "raw ore washing classification-sand separation, pre-concentration for discarding tailings in the mud selection system". This study conducted a systematic process test research on the recovery of Au, Ag, and Fe, analyzing the impact of process parameters on the various indicators. The results showed that the process achieved excellent technical indicators, and finally, an Au leaching rate of 88.99%, an Ag leaching rate of 31.52%, and an Fe recovery rate of 57.57% were respectively obtained in the whole process.